2014
DOI: 10.1074/jbc.m113.536326
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage within Reelin Repeat 3 Regulates the Duration and Range of the Signaling Activity of Reelin Protein

Abstract: Background:The physiological role of Reelin proteolysis is largely uncharacterized. Results: An "uncleavable" Reelin mutant remains active for a long time, and the cleaved Reelin fragment localizes differently than full-length Reelin. Conclusion: Extracellular and intracellular Reelin cleavage is required for halting downstream signaling and transport of the cleaved product. Significance: Inhibition of Reelin cleavage will be beneficial for treating neuropsychiatric diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 56 publications
4
47
0
Order By: Relevance
“…Mock control media were collected from non-Reelin construct transfected HEK293 cells, and purified by the same method as above (Sinagra et al, 2005;Rogers et al, 2013). Reelin is cleaved extracellularly at two sites, resulting in the generation of three major fragments: the N-terminus to repeat 2 (roughly 180 kDa), the central fragment from repeat 3-6 (roughly 190 kDa), and the C-terminal fragment consisting of repeats 7 and 8 (roughly 80 kDa) (Nakajima et al, 1997;de Rouvroit et al, 1999;Utsunomiya-Tate et al, 2000;Jossin et al, 2004Jossin et al, , 2007Krstic et al, 2012;Koie et al, 2014;Trotter et al, 2014). Additionally, two intermediate fragments are produced: one consisting of the N-terminus to repeat 6 (roughly 370 kDa), and one consisting of repeats 6-8 (roughly 270 kDa) (Jossin et al, 2004).…”
Section: Reelin Purificationmentioning
confidence: 99%
“…Mock control media were collected from non-Reelin construct transfected HEK293 cells, and purified by the same method as above (Sinagra et al, 2005;Rogers et al, 2013). Reelin is cleaved extracellularly at two sites, resulting in the generation of three major fragments: the N-terminus to repeat 2 (roughly 180 kDa), the central fragment from repeat 3-6 (roughly 190 kDa), and the C-terminal fragment consisting of repeats 7 and 8 (roughly 80 kDa) (Nakajima et al, 1997;de Rouvroit et al, 1999;Utsunomiya-Tate et al, 2000;Jossin et al, 2004Jossin et al, , 2007Krstic et al, 2012;Koie et al, 2014;Trotter et al, 2014). Additionally, two intermediate fragments are produced: one consisting of the N-terminus to repeat 6 (roughly 370 kDa), and one consisting of repeats 6-8 (roughly 270 kDa) (Jossin et al, 2004).…”
Section: Reelin Purificationmentioning
confidence: 99%
“…The N-R2 region has also been reported to bind alpha 3 beta 1 -integrins (Dulabon et al, 2000). Recently, it has been shown that reelin can be cleaved within the repeat 3 (R3) and that this produced N-terminal fragment is transported or diffuses to further regions than the larger fragments or full-length reelin (Koie et al, 2014). These results support a role of the N-terminal fragment in the range and duration of reelin signaling (Koie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These fragments are likely generated by two proteolytic cleavage events, occurring between Reelin repeats (R) R2-R3, and R6-R7 (Fig. 1A), as previously described for unpurified Reelin conditioned medium (29,37,40). These cleavage events could be the result of spontaneous protein processing or they could be due to the activity of miniscule amounts of proteases that co-purify with FL Reelin.…”
Section: Expression and Purification Of Full-length Reelin And Itsmentioning
confidence: 99%